Strategies and Effects of LEDS (Low Emission Development Strategy) in Fortaleza, Brazil - Cunha, Franciele; Barreto Neres, Camila; Franco Carvalho, Matheus (International Journal of Engineering and Management Sciences, 2021)
When it comes to climate change, the built environment, together with transport, and waste and water management play a significant role as Greenhouse Gases (GHG) emitting sectors, reflecting the strong need to address such issues by local governments. A notable action that has been taken in this regard is the Urban Low Emission Development Strategies (Urban LEDS), which consists of a project implemented by the UN-Habitat and the International Council for Local Environmental Initiatives (ICLEI) that selected eight model cities and twenty-one satellite cities around the world and aims to support integrated and ambitious climate action, encouraging low-carbon efforts in emerging economies through the collaboration among them. In addition, eight European cities also participated in the project in its first phase, contributing with their expertise and experience with climate change mitigation. Since 2012, the city of Fortaleza in Brazil is a model city of the Urban LEDS project and it has sustainably integrated and developed many projects, making it a more resilient city, stimulating its economic growth and improving its quality of life. This paper aims to present the milestones that Fortaleza has already met within Urban LEDS and its main priorities in the next years, identifying best practices in three European cities (Copenhagen, Zagreb and Hannover) that could also be implemented in its geographical, social and cultural context, as well as indicate lessons that other cities can learn from Fortaleza.